The PROSES MANUFAKTUR ROLL GILINGAN TEBU MENGGUNAKAN METODE PENGECORAN LOGAM - Pajar Agustian Akbar; Rilo Chandra Muhamadin (Universitas Muhammadiyah Gresik, 2025)
This study aims to analyze the manufacturing process of sugarcane mill rolls using the metal casting method at PT X. Sugarcane mill rolls are the main component in the sap extraction process so that material quality and dimensional accuracy greatly affect milling performance in sugar factories. The research method used is descriptive qualitative through direct observation of the production process, interviews with technicians, documentation, and analysis of the chemical composition of the material using spectrometric tests. The results show that the manufacturing process includes pattern making, sand mold making, metal melting, casting, natural cooling for 7–14 days, and machining processes consisting of facing, turning, boring, grooving, drilling, and finishing. The results of spectrometric tests on several samples indicate that the chemical composition of the material generally meets the FC 20 SP standard, although there are some values that are close to the tolerance limit. The machining process carried out with large-capacity machines and precision measuring instruments produces dimensions and surface quality of rolls that meet specifications, so that the resulting product is suitable for use in the sugar industry.